Wanderlust - Steel, Danielle (London Warner Books, 1994)
Orphaned when she was young, Audrey Driscoll has grown up caring for her eccentric millionaire grandfather and her demanding younger sister, Annabelle. As the 1930s unfold she decides to leave home, shocking friends, and outraging family.
Keywords: English fiction